Implementasi Pembelajaran Berbasis ICT (Information and Communication Technology) Sebagai Alat Bantu Komputer Multimedia untuk Meningkatkan Kompetensi Guru Serta Prestasi Belajar Siswa - Nursamsu, Nursamsu; Kusnafizal, Teuku (Jurnal Pendidikan Biologi, 2017)
This research aimed to increase teacherâs competition and studentsâ echievements in study with applied study based on ICT (information and communication technology) as a multimedia tool in learning process. This reseaarch used descriftiveÂ  method. The sample in this research were four teachers and and fourty four students. The technique to collect the data was observation, interview, and studentsâ score achievments. The result of this study that teachersâ statement in IPA subject said that activity by used ICT (information and communication technology) made students more interest and active in studying, than conventional study , but there were shortage in the activity especially to the facility that did not suitable so the study activity used ICT media ) information and communication technology) did not effective done. The score of studentsâ prestige in SMPN 1 Manyak Payed as 76,18% and SMPN 2 Karang Baru as 68,45% at Aceh Tamiang dthatistrict. It could be conclude that teachers had be done ICT media in learning process but not all the teachers used ICT because the facility did not complete meanwhile the studentâs prestige in SMPN 1 Manyak Payed higher than studentsâ prestige in SMPN 2 Karang Baru.